A Preliminary Exploration Using Imaging Methods to Predict the Possibility of the Recurrence of Serous Ovarian Cancer in Patients Undergoing Total Resection - Fang, Mengshi; Huang, Shan; Dong, Jiangning; Yan, Hong; Fang, Xin; Zhang, Ping; Cao, Feng; Chen, Yulan; Zhang, Qiujun (Frontiers in Oncology, 2022)
Background: The purpose of our research was to explore the value of preoperative CT and MRI examinations and clinical indicators in the prediction of recurrence of ovarian serous carcinoma in patients who underwent satisfactory staging surgery. Procedure: Detailed inclusion and exclusion criteria were installed to screen all patients collected and the eligible patients were divided into two groups. The CT and MRI features and some clinical characteristics of two groups were analyzed, in addition, the apparent diffusion coefficient (ADC) value in tumor solid region was measured. Univariate analysis was used in this study. Results: There were 78 patients with histologically proven ovarian serous carcinoma. According to the strict inclusion and exclusion criteria, we retained 29 patients (recurrence group: 11 patients, no recurrence group: 18 patients). For the peritoneal implantation metastasis in CT or MRI images and Ki67 proliferation index (Ki67 PI), the differences between two cohorts were statistically significant (P < 0.05). The rate of peritoneal metastasis in the recurrence cohort (10/11, 91%) was higher than that in the no recurrence cohort (7/18, 39%). Patients with high Ki-67 PI expression had lower recurrence risk than those with low Ki-67 PI expression, HR=0.172 (95%CI: 0.050-0.589, P=0.005), and patients without peritoneal planting had lower recurrence risk than those with it, HR=9.373 (95%CI: 1.194-73.551, P=0.033). For FIGO III patients, ipsilateral fallopian tube involvement was statistically significant between the two groups (P < 0.05). The differences in the other preoperative imaging characteristics of ovarian serous cancer, including the volume; capsule of the mass; main components; ADC value; cystic change; bleeding; degree of enhancement of the mainly solid region in 3 periods; and range of tumor involvement in the ovary, uterus, bladder, bowel, and pelvic wall, were not statistically significant. In addition, the differences in the other clinical indicators (i.e., age, FIGO stage) between the two cohorts were not statistically significant. Conclusions: In CT and MRI examinations before surgery, peritoneal implantation metastasis was suggestive of the possibility of recurrence of serous ovarian carcinoma in the near future. In addition to that, ipsilateral fallopian tube involvement and Ki67 PI may also indicate the possibility of recurrence.